Beauty Clinic Doctor's Views on Botulinum Toxin and Filler Injections from the Perspective of Qawā'id Fiqhiyyah - Az Zahra, Rahma Hanim; Najie', Ilyu 'Ainun (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
The Utilization of Botox and filler injections in beauty clinics is a subject of debate from both medical and Islamic legal perspectives. On the one hand, Botox and fillers are used for aesthetic purposes, such as reducing wrinkles and improving facial contours. On the other hand, they also have medical benefits, including overcoming hyperhidrosis and certain muscle disorders. This difference in purpose is what causes fiqh problems related to the halal status and validity of its use. This study aims to describe the views of beauty clinic doctors in Ponorogo on Botox and filler injections, and analyze them through the perspective of Qawā'id Fiqhiyyah. The method of this research is empirical juridical with a phenomenological approach. The data was collected through interviews, observation, and documentation. The analysis was carried out using the framework of Qawā'id Fiqhiyyah. The study's results reveal four categories of doctors' views: purpose-based/intended use, product-based halal, lifestyle trend-based, and public awareness-based. From the side of Qawā'id Fiqhiyyah, Botox and fillers are allowed if they are designed for treatment or legitimate needs, use halal ingredients, and are medically safe. However, its use solely for lifestyle or altering Allah's creation without shari'a reasons tends to be prohibited. Thus, the regulations pertaining to Botox and dermal fillers are contextual, depending on their purpose, ingredients, and impact on the patient’s well-being. Keywords: Botox Injections, Fillers, Beauticians, Qawā'id Fiqhiyyah.   Abstrak: Terdapat perdebatan tentang penggunaan injeksi Botox dan filler di klinik kecantikan dari aspek medis maupun hukum Islam. Di satu sisi, Botox dan filler digunakan untuk tujuan estetika seperti mengurangi kerutan dan memperbaiki kontur wajah; di sisi lain, keduanya juga memiliki manfaat medis, seperti mengatasi hiperhidrosis, dan gangguan otot tertentu. Perbedaan tujuan inilah yang menimbulkan problem fiqh terkait kehalalan dan keabsahan penggunaannya. Penelitian ini bertujuan untuk mendeskripsikan pandangan dokter klinik kecantikan di Ponorogo terhadap injeksi botox dan filler, serta menganalisisnya melalui perspektif Qawā‘Id Fiqhiyyah. Metode penelitian ini adalah yuridis empiris dengan pendekatan fenomenologis. Data dikumpulkan melalui wawancara,  observasi dan dokumentasi. Analisis dilakukan menggunakan kerangka Qawā‘Id Fiqhiyyah. Hasil penelitian menunjukkan empat kategori pandangan dokter, yaitu: berbasis tujuan/niat penggunaan, berbasis kehalalan produk, berbasis tren gaya hidup, serta berbasis kesadaran masyarakat. Dari sisi Qawā‘Id Fiqhiyyah, Botox dan filler diperbolehkan bila ditujukan untuk pengobatan atau kebutuhan sah, menggunakan bahan halal, serta aman secara medis. Namun, penggunaannya yang semata-mata untuk gaya hidup atau mengubah ciptaan Allah tanpa alasan syar‘i cenderung dilarang. Dengan demikian, hukum Botox dan filler bersifat kontekstual, bergantung pada tujuan, bahan, dan dampaknya terhadap kemaslahatan maupun kemudaratan pasien. Kata kunci: Injeksi Botox, Filler, Dokter Kecantikan, Qawā‘id Fiqhiyyah.